Is there a difference between power and endurance track and field runners according to their genetic predisposition in motivation and self-esteem? - Znazen, H.; Slimani, M.; Bragazzi, N.; Butovskaya, M.; Siala, H.; Messaoud, T.; Souissi, N. (Medicina dello Sport, 2021)
BACKGROUND: It is undeniable that success in competition has a strong psychological background, represented by mental toughness, tactical astuteness and motivation to endure pain during training and competition; however, the association between genetics and psychological state is still largely under-investigated. The aim of the present study was to examine the association between the angiotensin-converting enzyme (ACE) gene polymorphism and self-esteem and motivation in elite athletes. METHODS: Track and field athletes (47 males, 40 females; age: 20.55±2.22 years, body mass: 77.5±7.1 kg, height: 170.7±5.4 cm) competing at an international level, voluntarily participated in this study. The distribution of ACE genotypes was estimated. The athletes were prospectively classified into two groups according to their genetic polymorphism to physical efforts: endurance group (allele I, N.=48; 26 males, 22 females) and power group (allele D, N.=39; 24 males, 15 females). Motivation and Self-esteem were assessed using the Scale of Motivation in Sport (SMS-28) and the French version of the Physical Self Perception Profile (PSPP) before the commencement of competition in power and endurance athletes, respectively. RESULTS: The results showed that being carriers of D and I alleles was associated with intrinsic motivation to knowledge subscale. In addition, intrinsic motivation to stimulation subscale was associated with power athletes. Intrinsic motivation to stimulation and accomplish predicted performance of athletes who were carrying allele I and allele D. No significant difference in self-esteem subscales between power athletes (carrier of the allele D) and endurance athletes (carrier of the allele I) was observed. Thus, it has been shown that physical condition subscale predicted performance of power athletes who were carrying allele D. CONCLUSIONS: The present study indicates that individual differences in self-esteem and motivation depend on type of activities and may be genetically determined.